Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Sure, let's go through the problem step-by-step to compare the given equation [tex]\(x - \frac{y}{2} + 8 = 0\)[/tex] with the standard form [tex]\(ax + by + c = 0\)[/tex], and then find the value of [tex]\(2a + b - c\)[/tex].
1. Identify the coefficients:
The given equation is [tex]\(x - \frac{y}{2} + 8 = 0\)[/tex].
To identify coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], compare the given equation to the standard form [tex]\(ax + by + c = 0\)[/tex]:
- The coefficient of [tex]\(x\)[/tex] is [tex]\(a = 1\)[/tex].
- The coefficient of [tex]\(y\)[/tex] is [tex]\(b = -\frac{1}{2}\)[/tex].
- The constant term [tex]\(c = 8\)[/tex].
2. Calculate [tex]\(2a + b - c\)[/tex]:
Now that we have the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], we can substitute them into the expression [tex]\(2a + b - c\)[/tex].
Substitute [tex]\(a = 1\)[/tex], [tex]\(b = -\frac{1}{2}\)[/tex], and [tex]\(c = 8\)[/tex] into the expression:
[tex]\[ 2a + b - c = 2(1) + \left(-\frac{1}{2}\right) - 8 \][/tex]
3. Simplify the expression:
Step-by-step calculation:
[tex]\[ = 2 \cdot 1 + \left(-\frac{1}{2}\right) - 8 \][/tex]
First, calculate [tex]\(2 \cdot 1 = 2\)[/tex]:
[tex]\[ = 2 + \left(-\frac{1}{2}\right) - 8 \][/tex]
Then, add [tex]\(-\frac{1}{2}\)[/tex]:
[tex]\[ = 2 - \frac{1}{2} - 8 \][/tex]
Convert 2 to a fraction for easier subtraction:
[tex]\[ = \frac{4}{2} - \frac{1}{2} - 8 \][/tex]
Subtract the fractions:
[tex]\[ = \frac{4}{2} - \frac{1}{2} = \frac{3}{2} \][/tex]
Finally, subtract 8:
[tex]\[ \frac{3}{2} - 8 = \frac{3}{2} - \frac{16}{2} = \frac{3 - 16}{2} = \frac{-13}{2} = -6.5 \][/tex]
So, the value of [tex]\(2a + b - c\)[/tex] is [tex]\(-6.5\)[/tex].
1. Identify the coefficients:
The given equation is [tex]\(x - \frac{y}{2} + 8 = 0\)[/tex].
To identify coefficients [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], compare the given equation to the standard form [tex]\(ax + by + c = 0\)[/tex]:
- The coefficient of [tex]\(x\)[/tex] is [tex]\(a = 1\)[/tex].
- The coefficient of [tex]\(y\)[/tex] is [tex]\(b = -\frac{1}{2}\)[/tex].
- The constant term [tex]\(c = 8\)[/tex].
2. Calculate [tex]\(2a + b - c\)[/tex]:
Now that we have the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], and [tex]\(c\)[/tex], we can substitute them into the expression [tex]\(2a + b - c\)[/tex].
Substitute [tex]\(a = 1\)[/tex], [tex]\(b = -\frac{1}{2}\)[/tex], and [tex]\(c = 8\)[/tex] into the expression:
[tex]\[ 2a + b - c = 2(1) + \left(-\frac{1}{2}\right) - 8 \][/tex]
3. Simplify the expression:
Step-by-step calculation:
[tex]\[ = 2 \cdot 1 + \left(-\frac{1}{2}\right) - 8 \][/tex]
First, calculate [tex]\(2 \cdot 1 = 2\)[/tex]:
[tex]\[ = 2 + \left(-\frac{1}{2}\right) - 8 \][/tex]
Then, add [tex]\(-\frac{1}{2}\)[/tex]:
[tex]\[ = 2 - \frac{1}{2} - 8 \][/tex]
Convert 2 to a fraction for easier subtraction:
[tex]\[ = \frac{4}{2} - \frac{1}{2} - 8 \][/tex]
Subtract the fractions:
[tex]\[ = \frac{4}{2} - \frac{1}{2} = \frac{3}{2} \][/tex]
Finally, subtract 8:
[tex]\[ \frac{3}{2} - 8 = \frac{3}{2} - \frac{16}{2} = \frac{3 - 16}{2} = \frac{-13}{2} = -6.5 \][/tex]
So, the value of [tex]\(2a + b - c\)[/tex] is [tex]\(-6.5\)[/tex].
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.